2019
DOI: 10.3390/ma12091420
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of High Amylose Corn Starch–Microcrystalline Cellulose Aerogel with High Absorption

Abstract: Microcrystalline cellulose (MCC) aerogels were synthesized, blendingwith high amylose corn starch of different contents based on a NaOH–urea solution, and following by vacuum freeze-drying technology. The microstructure of the aerogel was observed by scanning electron microscopy (SEM) as an interconnected, porous three-dimensional structure, while X-ray diffractogram (XRD) measurements showed that the crystalline form was converted from cellulose I to cellulose II during dissolution and regeneration. Thermogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The silanized cellulose aerogel prepared by Nguyen et al has an adsorption capacities of 4~12 g/g for toluene and vacuum pump oil [32]. The maximum adsorption capacities of microcrystalline cellulose aerogel prepared by Luo et al to pump oil and linseed oil was 10.63 and 11.44 g/g [33]. The adsorption capacities of CMC/graphene oxide aerogel prepared by Xiang et al to organic solvents such as methanol is 10~21 g/g [34].…”
Section: Resultsmentioning
confidence: 99%
“…The silanized cellulose aerogel prepared by Nguyen et al has an adsorption capacities of 4~12 g/g for toluene and vacuum pump oil [32]. The maximum adsorption capacities of microcrystalline cellulose aerogel prepared by Luo et al to pump oil and linseed oil was 10.63 and 11.44 g/g [33]. The adsorption capacities of CMC/graphene oxide aerogel prepared by Xiang et al to organic solvents such as methanol is 10~21 g/g [34].…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogels are made by techniques such as solvent casting/particulate leaching [ 138 ], gas foaming [ 139 ], phase separation [ 140 ], melt molding [ 141 ], and freeze-drying [ 142 ] ( Figure 6 ). Hydrogels can be manufactured as films, coatings, nanoparticles, etc., and can act as semipermeable membranes through which fluid can flow in three dimensions.…”
Section: Various Strategies Of Anti-adhesionmentioning
confidence: 99%
“… Hydrogel fabrication techniques: ( a ) Solvent-casting/particulate-leaching [ 138 ]; ( b ) gas foaming [ 139 ]; ( c ) phase separation [ 140 ]; ( d ) melt molding [ 141 ]; and ( e ) freeze drying [ 142 ] (images adopted with permission). …”
Section: Figurementioning
confidence: 99%
“…They obtained sorption capacities between 14.67-18.90 g/g [2]. Luo et al (2019) used high amylose cornstarch-microcrystalline cellulose aerogel. They obtained a sorption ratio of 7.97-10.63 g/g for vacuum pump oil and 8.98-11.44 g/g for linseed oil, and the highest results were presented by the samples with a medium starch concentration [6].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Luo et al (2019) used high amylose cornstarch-microcrystalline cellulose aerogel. They obtained a sorption ratio of 7.97-10.63 g/g for vacuum pump oil and 8.98-11.44 g/g for linseed oil, and the highest results were presented by the samples with a medium starch concentration [6]. Long et al (2019) synthesized cellulose aerogels with sodium montmorillonite, and showed a sorption capacity between 4.5 g/g and 6 g/g for #48 and #220 lubricating oil [7].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%